BRCA1 and BRCA2 mutations in ovarian cancer patients from China: ethnic‐related mutations in BRCA1 associated with an increased risk of ovarian cancer. Issue 9 (23rd February 2017) - Shi, Tingyan; Wang, Pan; Xie, Caixia; Yin, Sheng; Shi, Di; Wei, Congchong; Tang, Wenbin; Jiang, Rong; Cheng, Xi; Wei, Qingyi; Wang, Qing; Zang, Rongyu
Abstract : BRCA1/2 are cancer predisposition genes involved in hereditary breast and ovarian cancer (HBOC). Mutation carriers display an increased sensitivity to inhibitors of poly(ADP‐ribose) polymerase (PARP). Despite a number of small‐size hospital‐based studies being previously reported, there is not yet, to our knowledge, precise data of BRCA1/2 mutations among Chinese ovarian cancer patients. We performed a multicenter cohort study including 916 unselected consecutive epithelial ovarian cancer (EOC) patients from eastern China to screen for BRCA1/2 mutations using the next‐generation sequencing approach. A total of 153 EOC patients were found to carry pathogenic germline mutations in BRCA1/2, accounting for an overall mutation incidence of 16.7% with the predominance in BRCA1 (13.1%) compared with BRCA2 (3.9%). We identified 53 novel pathogenic mutations, among which the c.283_286delCTTG and the c.4573C > T of BRCA1 were both found in two unrelated patients. More importantly, the most common mutation found in this study, c.5470_5477del8 was most likely to be Chinese population‐related without an apparent founder origin. This hot‐spot mutation was presumably associated with an increased risk of ovarian cancer. Taken together, germline BRCA1/2 mutations were common in Chinese EOC patients with distinct mutational spectrum compared to Western populations. Our study contributes to the current understanding of BRCA1/2 mutation prevalence worldwide. We recommend BRCA1/2 genetic testing to all Chinese women diagnosed with EOC to identify HBOC families, to provide genetic counseling and clinical management for at‐risk relatives. Mutation carriers may also benefit from PARP‐targeted therapies. Abstract : What's new? Mutations in BRCA1 and BRCA2 are well‐characterized predisposing factors in ovarian cancer. Recent studies suggest, however, that their incidence varies considerably between ethnic populations. In the present evaluation of BRCA1/2 mutational spectrum in Chinese women with epithelial ovarian cancer, pathogenic mutations were found to occur in more than 16% of cases. Next‐generation sequencing further led to the identification of novel pathogenic mutations and Chinese ethnic‐related hot‐spot variations. Such novel insights into population‐based BRCA1/2 mutational prevalence and characteristics can potentially aid genetic counseling and the selection of patients who stand to benefit from poly (ADP‐ribose) polymerase‐targeted therapy.